Using behavioral observation for the longitudinal study of anger regulation in middle childhood. Issue 2 (3rd April 2019) - Kirsch, Fabian; Busching, Robert; Rohlf, Helena; Krahé, Barbara
ABSTRACT: Assessing anger regulation via self-reports is fraught with problems, especially among children. Behavioral observation provides an ecologically valid alternative for measuring anger regulation. The present study uses data from two waves of a longitudinal study to present a behavioral observation approach for measuring anger regulation in middle childhood. At T1, 599 children from Germany (6–10 years old) were observed during an anger eliciting task, and the use of anger regulation strategies was coded. At T2, 3 years later, the observation was repeated with an age-appropriate version of the same task. Partial metric measurement invariance over time demonstrated the structural equivalence of the two versions. Maladaptive anger regulation between the two time points showed moderate stability. Validity was established by showing correlations with aggressive behavior, peer problems, and conduct problems (concurrent and predictive criterion validity). The study presents an ecologically valid and economic approach to assessing anger regulation strategies in situ.